Perceived neighborhood safety and asthma morbidity in the School Inner‐City Asthma Study. Issue 1 (13th January 2014) - Kopel, Lianne S.; Gaffin, Jonathan M.; Ozonoff, Al; Rao, Devika R.; Sheehan, William J.; Friedlander, James L.; Permaul, Perdita; Baxi, Sachin N.; Fu, Chunxia; Subramanian, S.V.; Gold, Diane R.; Phipatanakul, Wanda
Summary Aim The aim of this study was to investigate whether neighborhood safety as perceived by primary caregivers is associated with asthma morbidity outcomes among inner‐city school children with asthma. Methods School children with asthma were recruited from 25 inner‐city schools between 2009 and 2012 for the School Inner‐City Asthma Study (N = 219). Primary caregivers completed a baseline questionnaire detailing their perception of neighborhood safety and their children's asthma symptoms, and the children performed baseline pulmonary function tests. In this cross‐sectional analysis, asthma control was compared between children whose caregivers perceived their neighborhood to be unsafe versus safe. Results After adjusting for potential confounders, those children whose primary caregivers perceived the neighborhood to be unsafe had twice the odds of having poorly controlled asthma (odds ratio [OR] adjusted = 2.2, 95% confidence interval [CI] = 1.2–3.9, P = 0.009), four times the odds of dyspnea and rescue medication use (OR adjusted = 4.7; 95% CI = 1.7–13.0, P = 0.003, OR adjusted = 4.0; 95% CI = 1.8–8.8, P < 0.001, respectively), three times as much limitation in activity (OR adjusted = 3.2; 95% CI = 1.4–7.7, P = 0.008), and more than twice the odds of night‐time symptoms (OR adjusted = 2.2; 95% CI = 1.3–4.0, P = 0.007) compared to participants living in safe neighborhoods. There was no difference in pulmonary function test results between the two groups. Conclusions Primary caregivers' perception of neighborhood safety is associated with childhood asthma morbidity among inner‐city school children with asthma. Further study is needed to elucidate mechanisms behind this association, and future intervention studies to address social disadvantage may be important. Pediatr Pulmonol. 2015; 50:17–24. © 2014 Wiley Periodicals, Inc.